A taxonomic revision of the hover wasp genus Eustenogaster van der Vecht (Insecta: Hymenoptera; Vespidae, Stenogastrinae) - Saito, Fuki; Kojima, Jun-Ichi (Zootaxa, 2007)
A taxonomic revision is given for the stenogastrine genus Eustenogaster van der Vecht, 1969, which is distributed from India to Southeast Asia and southern China. A total of 15 species, including three new species (E. fumipennis Saito, sp. nov., E. latebricola Saito, sp. nov. and E. spinicauda Saito, sp. nov.), are recognized in the genus. A key to species, descriptions of the new species, and notes on taxonomic status, morphological characters and distribution records of the previously described taxa are given.